Theory of Truncation Resonances in Continuum Rod‐Based Phononic Crystals with Generally Asymmetric Unit Cells (Adv. Theory Simul. 2/2023). Issue 2 (10th February 2023) - Al Ba'ba'a, Hasan B.; Willey, Carson L.; Chen, Vincent W.; Juhl, Abigail T.; Nouh, Mostafa
Abstract : Resonant modes emerging within bandgaps, or truncation resonances, represent a unique phenomenon of phononic materials and play a central role in flow control, edge/surface modes and sensing applications. In article 2200700, Mostafa Nouh and co‐workers establish the fundamental factors that contribute to the origination or suppression of truncation resonances and provides an interpretation of localized vibrational modes in finite phononic crystals.